2009
DOI: 10.1177/0363546509333010
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Avulsion of the Medial Patellofemoral Ligament after Primary Traumatic Patellar Dislocation Predicts Subsequent Instability in Men

Abstract: An MPFL avulsion at the femoral attachment in primary traumatic patellar dislocations predicts subsequent patellar instability. The authors suggest that MPFL injury location be taken into account when planning treatment of primary traumatic patellar dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 37 publications
4
110
2
4
Order By: Relevance
“…Individuals with a rupture of the MPFL possess a greater risk of recurrent patellar instability compared to those whose MPFL remain intact [45]. Since the MPFL may not be ruptured in all cases following FTPD even though there may be an elongation or partial tear, there may have been a difference between the groups in the proportion of MPFL deficit in each group [46,47]. This remains unknown as MRI was not normally undertaken as routine in the three study centres.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a rupture of the MPFL possess a greater risk of recurrent patellar instability compared to those whose MPFL remain intact [45]. Since the MPFL may not be ruptured in all cases following FTPD even though there may be an elongation or partial tear, there may have been a difference between the groups in the proportion of MPFL deficit in each group [46,47]. This remains unknown as MRI was not normally undertaken as routine in the three study centres.…”
Section: Discussionmentioning
confidence: 99%
“…33,51 Recurrent instability (including redislocation and painful subluxation) and complete dislocation are reported in up to one-third and one-half of patients, respectively, treated nonoperatively after traumatic, acute lateral patellar dislocation. 38 Likewise, MPFL rupture is considered the essential lesion of chronic lateral patellar instability. 24 MPFL reconstruction has become a popular procedure to restore normal patellar tracking, prevent symptoms of instability, and limit risk of chondral injury in patients with chronic lateral patellar instability who have failed nonoperative measures.…”
mentioning
confidence: 99%
“…21 Higher rates of redislocation and surgical intervention were seen in these groups of patients. 22 As a whole, first-time dislocators were found to have a low rate of subsequent dislocation. 23 Many studies have shown no significant differences in nonsurgical and surgical treatment groups on long term followup.…”
Section: Nonoperative Treatmentmentioning
confidence: 95%